Impact of SOx, NOx and NH3 emission reductions on PM2.5 concentrations across Europe: Hints for future measure development. (November 2021) - Clappier, A.; Thunis, P.; Beekmann, M.; Putaud, J.P.; de Meij, A.
Highlights: For moderate reductions, emission and P M concentration changes are linearly linked. Reducing S O 2 emissions where abundant is always efficient. Reducing N H 3 emissions is more efficient where it is less abundant. Reducing N O x emissions where N O x are abundant can be counter-productive. Both N O x and N H 3 regimes occur in some regions, calling for combined reductions Abstract: Given the remaining air quality issues in many European regions, smart air quality strategies are necessary to reduce the burden of poor air quality. While designing effective strategies for non-reactive primary pollutants is straightforward, this is not the case for secondary pollutants for which the relationship between emission changes and the resulting concentration changes can be nonlinear. Under such conditions, strategies targeting the largest emitting sources might not be the most effective. In this work, we provide elements to better understand the role of the main emission precursors ( S O 2, N O x, N H 3 ) on the formation of secondary inorganic aerosols. By quantifying the P M 2.5 sensitivity to emission reductions for each of these three precursors, we define and quantify the intensity of P M 2.5 formation chemical regimes across Europe. We find that for emission reductions limited to 25%, the relation between emission and P M concentration changes remain mostly linear, with the exception of the Po Valley where non-linearities reach more than 30% in winter. When emission reductions increase to 50%, non-linearity reaches more than 60% in the Po Valley but stay below 30% in the rest of Europe. In terms of implications on abatement strategies, our findings can be summarized in the following key messages: (1) reducing S O 2 emissions where abundant is always efficient (e.g. eastern Europe and Balkans); (2) reducing N H 3 emissions is more efficient where it is less abundant (e.g. the Po basin) than where it is abundant, given the limiting role of N H 3 in the P M formation; (3) reducing N O x emissions where N O x are abundant can be counter-productive with potential increases of P M due to the increased oxidant capacity of the atmosphere (e.g. Po valley); (4) because regions with both N H 3 and N O x sensitive chemical regimes are mixed within countries, both need to be reduced together, as pollution reduction policies need at least to be defined at a country level; (6) while for N H 3 the focus is clearly on wintertime, it is the whole year for N O x . The simulations proposed in this work could be used as benchmark for other models as they constitute the type of scenarios required to support air quality strategies. In addition, the straight and systematic emission reductions imposed for the scenarios in this work are well suited for a better understanding of the behavior of the model, in terms of responses to emission reductions.